Herniation of Small Bowel Loop through a Broad Ligament Defect Masquerading as Torsion of Ovarian Cyst - Babatola Bakare; Olumide Akadiri; Akinyemi Akinsoji Akintayo (Case Reports in Obstetrics and Gynecology)
Torsion of ovarian cyst is a common cause of acute abdomen especially in women of reproductive age-group. It commonly presents with colicky abdominal pain associated with nausea and vomiting. It could however mimic acute intestinal obstruction. The patient was a 32-year-old multipara with no previous history of pelvic or abdominal surgery. She was admitted with colicky lower abdominal pain associated with repeated episodes of vomiting and nausea. Laboratory investigations were essentially normal. Abdominopelvic USS showed a hypoechoic mass lesion in the left adnexium measuring 7.1 × 5.5 cm; surrounding bowel loops were hypoactive, dilated, and fluid filled. Diagnosis of acute abdomen secondary to suspected torsion of ovarian cyst was made. Management began for acute abdomen with intravenous hydration, prophylactic antibiotics, and analgesics. An emergency laparotomy revealed about 6 cm defect in the left broad ligament in which a 20 cm segment of terminal ileum was encased. Liberation of the ileal segment was done and the broad ligament defect closed. Bowel obstruction requires high index of suspicion in a patient with acute abdomen due to suspected torsion ovarian cyst most especially in the absence of previous pelvic or abdominal surgery.